1990
DOI: 10.1111/j.1528-1157.1990.tb05874.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Aspects of Learning Disabilities in Epilepsy

Abstract: Cognitive impairment is regarded as the link between epileptic conditions and the inability to learn in school. The neuropsychological approach to learning disabilities in epilepsy, therefore, first concentrates on analyzing the differential effects of epileptic factors on cognitive function. The impact of seizure activity, localization of epileptogenic foci, and antiepileptic treatment on cognitive functioning can be evaluated based upon the results of continuous assessment with a computerized neuropsychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
63
0
13

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 48 publications
5
63
0
13
Order By: Relevance
“…Evidence of these deficits has been reported immediately after diagnosis and before initiation of AED treatment (Aldenkamp et al 1990, Mandelbaum andBurack 1997). Specifically, it was found that children with AS achieved lower scores than children with other types of epilepsy (generalized GTCS, partial epilepsies, benign forms of childhood epilepsy) on 11 of the 12 tests for information processing, attention, memory, and motor speed administered before initiation of drug therapy (Aldenkamp et al 1990). The authors suggested that this finding may be explained by greater central nervous system dysfunction associated with AS and ongoing seizure activity that may interfere with developmental progress because of time spent in an unresponsive state.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Evidence of these deficits has been reported immediately after diagnosis and before initiation of AED treatment (Aldenkamp et al 1990, Mandelbaum andBurack 1997). Specifically, it was found that children with AS achieved lower scores than children with other types of epilepsy (generalized GTCS, partial epilepsies, benign forms of childhood epilepsy) on 11 of the 12 tests for information processing, attention, memory, and motor speed administered before initiation of drug therapy (Aldenkamp et al 1990). The authors suggested that this finding may be explained by greater central nervous system dysfunction associated with AS and ongoing seizure activity that may interfere with developmental progress because of time spent in an unresponsive state.…”
Section: Discussionmentioning
confidence: 94%
“…Although neuropsychological studies of individuals with epilepsy have not demonstrated a specific pattern of impairment, deficits in attention, memory, and language, as well as speed of information processing, have been documented (Seidenberg et al 1988, Aldenkamp et al 1990, Forsythe et al 1991, Stores 1992, Deonna et al 2000, Henkin et al 2003). These cognitive deficiencies were postulated to be responsible for the poorer performance in skills such as reading, spelling, arithmetic, and comprehension that has been observed in children with epilepsy (Seidenberg et al 1986, Seibelink et al 1988, Sturniolo and Galletti 1994, Austin et al 1999, Bailet and Turk 2000.…”
mentioning
confidence: 99%
“…Sinais cada vez mais sutis do comprometimento das funções cerebrais são diagnosticados 18 . Os distúrbios da inteligência têm sido associados com epilepsia a partir de uma ruptura na função cerebral, mas as inter-relações entre função cognitiva e condição epiléptica são extremamente complexas 15 .…”
Section: Discussionunclassified
“…A idade precoce do início das crises pode interferir no desenvolvimento cerebral e, por conseqüência, provocar, a longo prazo, impacto na cognição por inibição na atividade mitótica, afetando a mielinização e reduzindo o número de células. Por isso é pior o prognóstico para o desenvolvimento cognitivo nas encefalopatias idade-dependente 15 . Seidenberg et al 16 correlacionaram a alta incidência de problemas escolares com epilepsia, sendo que crianças epilépticas apresentaram menor desempenho escolar.…”
unclassified
“…Learning and behavioral problems are more common in children with epilepsy than in the general population (2,3). In addition, children with known epileptogenic conditions have more LDs than do children with idiopathic or cryptogenic epilepsies (4).…”
mentioning
confidence: 99%